In search of the missing light: a book about not giving up (Educational Technologies Ltd Place of publication not identified, 2004)
"In Search of the Missing Light: A Book About Not Giving Up" follows the inspiring journey of a young firefly named Flicker, who is determined to find the source of the light that has gone missing in his forest. Despite facing challenges and obstacles along the way, Flicker refuses to give up. With the support of his friends$1 (Ba wise owl, a playful squirrel, and a brave mouse$1 (BFlicker learns valuable lessons about perseverance, resilience, and the importance of teamwork. As they embark on their adventure, they discover that sometimes the journey itself is as important as the destination, and that determination can lead to unexpected rewards.s